Core Judgments of Instructional Designers in Practice. Issue 3 (23rd October 2017) - Boling, Elizabeth; Alangari, Husa; Hajdu, Ilona Marie; Guo, Meize; Gyabak, Khendum; Khlaif, Zuheir; Kizilboga, Remzi; Tomita, Kei; Alsaif, Manal; Lachheb, Ahmed; Bae, Haesol; Ergulec, Fatih; et al.
Abstract : The tacit beliefs that affect all the judgments made during the design process (core judgments) of 11 practicing instructional designers were studied via their discussions of strong and weak designs during interviews. Transcripts were analyzed from a phenomenological perspective. The study demonstrates that while designer judgment is rarely discussed in the field, these designers do appear to bring core judgments to bear on their designing, and these judgments are complex in nature. Researchers argue that core judgment, unaccounted for in rational models of instructional design, requires further attention from scholars and design educators.